Randomized Sham-Controlled Trial of Navigated Repetitive Transcranial Magnetic Stimulation for Motor Recovery in Stroke: The NICHE Trial. Issue 9 (September 2018) - Harvey, Richard L.; Edwards, Dylan; Dunning, Kari; Fregni, Felipe; Stein, Joel; Laine, Jarmo; Rogers, Lynn M.; Vox, Ford; Durand-Sanchez, Ana; Bockbrader, Marcia; Goldstein, Larry B.; Francisco, Gerard E.; et al.
Abstract : Background and Purpose─: We aimed to determine whether low-frequency electric field navigated repetitive transcranial magnetic stimulation to noninjured motor cortex versus sham repetitive transcranial magnetic stimulation avoiding motor cortex could improve arm motor function in hemiplegic stroke patients when combined with motor training. Methods─: Twelve outpatient US rehabilitation centers enrolled participants between May 2014 and December 2015. We delivered 1 Hz active or sham repetitive transcranial magnetic stimulation to noninjured motor cortex before each of eighteen 60-minute therapy sessions over a 6-week period, with outcomes measured at 1 week and 1, 3, and 6 months after end of treatment. The primary end point was the percentage of participants improving ≥5 points on upper extremity Fugl-Meyer score 6 months after end of treatment. Secondary analyses assessed changes on the upper extremity Fugl-Meyer and Action Research Arm Test and Wolf Motor Function Test and safety. Results─: Of 199 participants, 167 completed treatment and follow-up because of early discontinuation of data collection. Upper extremity Fugl-Meyer gains were significant for experimental ( P <0.001) and sham groups ( P <0.001). Sixty-seven percent of the experimental group (95% CI, 58%–75%) and 65% of sham group (95% CI, 52%–76%) improved ≥5 points on 6-month upper extremity Fugl-Meyer ( P =0.76). There was also no difference between experimental and sham groups in the Action Research Arm Test ( P =0.80) or the Wolf Motor Function Test ( P =0.55). A total of 26 serious adverse events occurred in 18 participants, with none related to the study or device, and with no difference between groups. Conclusions─: Among patients 3 to 12 months poststroke, goal-oriented motor rehabilitation improved motor function 6 months after end of treatment. There was no difference between the active and sham repetitive transcranial magnetic stimulation trial arms. Clinical Trial Registration─: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02089464. Abstract : Supplemental Digital Content is available in the text.